Pengaruh Kepemimpinan Transformasional Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Pt. Jaya Tehnik Logam - Febrian Ibra Puadi; Lilis Suryani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine the influence of transformational leadership and work discipline on employee performance at PT. Jaya Metal Engineering. The research method used is a quantitative method with an associative approach. data collection through the distribution of questionnaires to the entire population as many as 60 sampling techniques using saturated sampling techniques and obtained as many as 60 respondents and also random sampling techniques for pre-surveys with 15 respondents. The data analysis techniques used in this study include validity test, reliability test, normality test, classical assumption test, linear regression analysis, correlation coefficient test, determination coefficient, and hypothesis test. The results of the study show that Transformational Leadership (X1) has a positive and significant effect on employee performance partially. It is shown from the t-value calculated > t table (6,075 > 1,671) and the significance value of 0.000 < 0.05 and the regression equation Y = 22.539 + 0.434X1, the correlation value is 0.624, the determination coefficient value is 38.9%. Work discipline (X2) has a positive and significant effect on employee performance is partially indicated from the t-value of the table > t-table (6,544 > 1,671) and the significance value of 0.000 < 0.05, as well as the regression equation Y = 21.276 + 0.464X2, the correlation value is 0.652, and the determination coefficient value is 65.2%. Transformational Leadership (X1) and Work Discipline (X2) simultaneously had a positive and significant effect on work performance as shown from the value of f calculated > f table (73.484 > 3.159) and significance value of 0.000 < 0.05, as well as the regression equation Y = 8.380 + 0.382X1 + 0.414X2, the correlation value was 0.849, the determination coefficient value was 72.1%.